Modulated Laser Cladding of Implant-Type Coatings by Bovine-Bone-Derived Hydroxyapatite Powder Injection on Ti6Al4V Substrates—Part I: Fabrication and Physico-Chemical Characterization - Mocanu, Aura-Cătălina; Miculescu, Florin; Stan, George E.; Pasuk, Iuliana; Tite, Teddy; Pascu, Alexandru; Butte, Tudor Mihai; Ciocan, Lucian-Toma (MDPI AG, 2022)
The surface physico-chemistry of metallic implants governs their successful long-term functionality for orthopedic and dentistry applications. Here, we investigated the feasibility of harmoniously combining two of the star materials currently employed in bone treatment/restoration, namely, calcium-phosphate-based bioceramics (in the form of coatings that have the capacity to enhance osseointegration) and titanium alloys (used as bulk implant materials due to their mechanical performance and lack of systemic toxicity). For the first time, bovine-bone-derived hydroxyapatite (BHA) was layered on top of Ti6Al4V substrates using powder injection laser cladding technology, and then subjected, in this first stage of the research, to an array of physical-chemical analyses. The laser processing set-up involved the conjoined modulation of the BHA-to-Ti ratio (100 wt.% and 50 wt.%) and beam power range (500–1000 W). As such, on each metallic substrate, several overlapped strips were produced and the external surface of the cladded coatings was further investigated. The morphological and compositional (SEM/EDS) evaluations exposed fully covered metallic surfaces with ceramic-based materials, without any fragmentation and with a strong metallurgical bond. The structural (XRD, micro-Raman) analyses showed the formation of calcium titanate as the main phase up to maximum 800W, accompanied by partial BHA decomposition and the consequential advent of tetracalcium phosphate (markedly above 600 W), independent of the BHA ratio. In addition, the hydrophilic behavior of the coatings was outlined, being linked to the varied surface textures and phase dynamism that emerged due to laser power increment for both of the employed BHA ratios. Hence, this research delineates a series of optimal laser cladding technological parameters for the adequate deposition of bioceramic layers with customized functionality.
Keywords: laser cladding; bioceramic coating; biological HA; powder injection; laser power